Neo-Confucian Sensory Readings of Scriptures: The Reading Methods of Chu Hsi and Yi Hwang. Issue 1 (3rd July 2017) - Yoo, Yohan
Abstract : Chu Hsi (1130-1200) of China and Yi Hwang (1501–1570) of Korea, leading scholars of the Neo-Confucian school of the two countries, emphasized readings of Confucian scriptures. They believed that Confucian scriptures have transformative power when read repeatedly and deliberately. Chu introduced the concept—further developed by Yi—of encouraging a scholar to activate at least three senses when reading a text, over and above the experience of merely reading the characters of the text. They advised Neo-Confucian scholars to try to make contact with the sages and fully internalize their teaching through their senses of sight, hearing, and taste by reading scriptures, though they did not directly appeal to the physical senses. First, the text should be recited aloud so the reciters will hear their own voices, sometimes along with those of their colleagues when several scholars read together. They imagined, furthermore, that the voices they were hearing while reading were those of the ancient sages themselves. Secondly, while hearing the voices of the sages, the reciting scholars should visualize their images, seeking personal communion with them. Finally, the meditative reading of scholars was frequently likened to savoring a text's flavor. The act of reading books was described as eating, biting, chewing, and tasting. When the readers recited the text aloud, pronouncing each syllable using tongues, lips and mouths, they were engaged in a gustatory experience: "chewing" and "tasting" scriptures.